Reading in the book picnic hearts By Muhammad bin Aziz al-Sijistani His method, and his semantic research - حمّاديّ عليّ حسين حمّاديّ (Journal of College of Education, 2023)
The strange topic of the Qur’an is one of the oldest topics of concern to the Islamic community. Previous studies of the book (Nuzhat al-Qulub) were optional studies of strange vocabulary, and they did not develop a comprehensive approach to the noble Qur’an text . As for Muhammad bin Aziz al-Sijistani, he devised a method for himself that he had not previously done, as he divided the book according to the letters of the dictionary first, then according to the movement of the first letter second, then according to its appearance in the Holy Qur’an text third. The author of the book did not delete the letters of the ziyadah from the Qur’an vocabulary, but rather arranged it according to the way it appears in the noble Qur’an text. Therefore, whoever searches for the meaning of a vocabulary in the book, finds it difficult to find the term if he is not familiar with the author’s . Al-Sijistani in his interpretation of the Qur’anic vocabulary begins by clarifying the meaning of the singular by interpreting it with a noble Qur’anic verse, which is what is termed (interpretation of the Qur’an with the Qur’an). It is noticeable that the author mentioned in his book some vocabulary that was not mentioned in the noble Qur’an text, in addition to neglecting to mention some Qur’anic vocabulary.